2004
DOI: 10.1021/jm0310129
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of New Templates Derived from Pyrrolopyrimidine as Selective Multidrug-Resistance-Associated Protein Inhibitors in Multidrug Resistance

Abstract: In our continued effort to identify selective MRP1 modulators, we have developed two novel templates, 3 and 4, through rational drug design by identifying the key pharmacophore interaction at the 7-position of the pyrrolopyrimidine template 1. Further synthesis and SAR work on these novel templates gave a number of potent MRP1 modulators with great selectivity against Pgp. Additional studies to reduce the CYP3A4 inhibition are also reported. Several compounds of these classes were subjected to in vivo xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…Interestingly, some of them were rather specific for MRP1 over P-glycoprotein, and displayed limited interactions with enzymes involved in drug metabolism such as cytochrome P450s. A few compounds exhibited acceptable pharmacokinetics, and appeared indeed active in vivo as shown by trials on xenografted mice models where they potentiated the cytotoxic effects of vincristine 81,82 In an independent and unrelated study, Benyahia et al reported the ability of the antiinflammatory drug, indomethacin (Fig. 7), to chemosensitize MRP1-overexpressing cells to vincristine and etoposide.…”
Section: Raloxifene-based Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some of them were rather specific for MRP1 over P-glycoprotein, and displayed limited interactions with enzymes involved in drug metabolism such as cytochrome P450s. A few compounds exhibited acceptable pharmacokinetics, and appeared indeed active in vivo as shown by trials on xenografted mice models where they potentiated the cytotoxic effects of vincristine 81,82 In an independent and unrelated study, Benyahia et al reported the ability of the antiinflammatory drug, indomethacin (Fig. 7), to chemosensitize MRP1-overexpressing cells to vincristine and etoposide.…”
Section: Raloxifene-based Inhibitorsmentioning
confidence: 99%
“…6). [81][82][83][84] The best derivatives exhibited high efficiency to inhibit MRP1, with half-maximal values in the range 0.02-0.2 mM towards daunomycin cellular efflux and cell growth sensitization to doxorubicin. Interestingly, some of them were rather specific for MRP1 over P-glycoprotein, and displayed limited interactions with enzymes involved in drug metabolism such as cytochrome P450s.…”
Section: Raloxifene-based Inhibitorsmentioning
confidence: 99%
“…MRP1 was discovered more than 15 years after P-glycoprotein, and thus it is not surprising that fewer MRP1-specific modulators have been identified (Cole et al, 1992;Chen et al, 2001;Wang et al, 2004;Boumendjel et al, 2005;Norman et al, 2005). Similar to P-glycoprotein, MRP1 can confer resistance to natural product drugs in tumor cells (Cole et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Much interest in this heterocyclic moiety has arisen in recent pharmacological programs as it serves as a bioisoster of indole or purine. [7][8][9][10][11][12][13][14][15][16] Applications in the preparation of bioactive molecules and in the syntheses of dopamine D-4 receptor ligands [17] as well as of potent GnRH antagonists [18] have been cited. The increased interest in this heterocyclic system has motivated considerable synthetic efforts towards functionalized azaindole derivatives.…”
Section: Introductionmentioning
confidence: 99%